2009
DOI: 10.17796/jcpd.33.3.c244761467507721
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Lip and Palate: Association with Other Congenital Malformations

Abstract: Orofacial clefts are frequently associated with other congenital malformations. Studies vary in incidence and types of anomalies. Objective: To evaluate associated malformations in orofacial cleft patients at a major research hospital. Study Design: Medical records of 1127 patients, in the Cleft Palate / Craniofacial Clinic, Boys Town National Research Hospital, from January 1980 through February 2000 were reviewed. Patients were divided into two categories: 1) cleft palate only (CP), and 2) cleft lip, with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
41
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 5 publications
6
41
1
3
Order By: Relevance
“…Changes in these biometric jaw parameters may result from a disturbance intrinsic to the mandibular area or may be part of a skeletal/neuromuscular disease. Alternatively, they bildungen von Lippen, Kiefer und Gaumen kombiniert [3,15,42,43,44]. Während Spaltbildungen der Lippe und des Oberkiefers heute sonographisch bereits sehr zuverlässig festgestellt werden können [6,24,25,30,37,53,54], gelingt die Detektion von isolierten Gaumenspalten, die besonders oft mit weiteren Fehlbildungen assoziiert sein können, meist nicht [26].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Changes in these biometric jaw parameters may result from a disturbance intrinsic to the mandibular area or may be part of a skeletal/neuromuscular disease. Alternatively, they bildungen von Lippen, Kiefer und Gaumen kombiniert [3,15,42,43,44]. Während Spaltbildungen der Lippe und des Oberkiefers heute sonographisch bereits sehr zuverlässig festgestellt werden können [6,24,25,30,37,53,54], gelingt die Detektion von isolierten Gaumenspalten, die besonders oft mit weiteren Fehlbildungen assoziiert sein können, meist nicht [26].…”
Section: Discussionunclassified
“…Screening in this timeframe is specifically performed to identify structural anomalies, syndromic malformations, and chromosomal disturbances. Many of the above findings are combined with cleft formation in lips, jaws, and palate [3,15,42,43,44]. While cleft formation in the lip and maxilla can today be diagnosed very reliably by sonography [6,24,25,30,37,53,54], attempts to detect isolated cases of cleft palate will often fail, which is unfortunate because they are often associated with other malformations [26].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of genes are being identified as playing a causal role in these syndromic cases. Importantly however, it is clear that even in cases considered nonsyndromic, CL/P preferentially co-occurs with a range of other clinical presentations including congenital heart defects, mild structural brain anomalies, subtle cognitive deficits, and altered pituitary function (Laron and Opitz, 1969; Roitman and Laron, 1978; Rudman et al, 1978; Nopoulos et al, 2002; Swanenburg de Veye et al, 2003; Conrad et al, 2008; Beriaghi et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A European study of 3860 patients with cleft lip (CL) or combined cleft lip and palate (CLP) identified malformations of the cardiovascular system in at least 7% of patients, not including those with recognized syndromes and chromosomal abnormalities (Calzolari et al, 2007). Regional epidemiological studies have revealed the same trend in the Middle East (Rawashdeh and Jawdat Abu-Hawas, 2008;Beriaghi et al, 2009;Altunhan et al, 2011;Yazdee et al, 2011). For example, nearly 25% of 121 cleft palate (CP) and CLP patients in a Turkish study had a cardiovascular anomaly, representing the most common congenital defect in this population (Altunhan et al, 2011).…”
mentioning
confidence: 99%